Demand for assistance in a human milk bank associated with socioeconomic and maternal-child health factors in Viçosa - Minas Gerais - Fonseca, Rafaela Mara Silva; Ayres, Lilian Fernandes Arial; Milagres, Luana Cupertino; Franceschini, Sylvia do Carmo Castro; Henriques, Bruno David (Ciência e Natura, 2022)
The superiority of breast milk over milk of other species is already consolidated and there are numerous benefits in the practice of breastfeeding. The Human Milk Bank is a privileged place for the establishment of breastfeeding, as actions to encourage, support and promote breastfeeding are developed. This is a cross-sectional, retrospective study carried out at the only maternity hospital in the city. The sample consisted of mothers and babies assisted by a lactation support program from 2005 to 2016 and also mothers and babies monitored by the human milk bank. It was observed that the assistance of the milk bank was associated with the type of delivery performed (cesarean) (OR: 2.11; 95% CI: 1.03-4.33), having premature children (gestational age) (OR: 3 , 48; 95% CI: 1.52-7.95), higher education (OR: 1.16; 95% CI: 1.03-1.32) and being younger (age) (OR: 0.94; 95% CI %: 0.88-0.99) were the indicators that increased the mother’s chance to seek care from the milk bank, regardless of parity and place of residence. The support, protection and promotion of breastfeeding that is carried out in this place, is configured as an important scenario favoring this practice, impacting on the health of the mother-child binomial in the present and in the future.